Analisis Ketepatan Pengukur Tegangan True RMS Jala-Jala Listrik Berbasis Mikrokontroler ATmega 328P - Farobi Widia Nanda; Freddy Kurniawan; Paulus Setiawan (Institut Teknologi Dirgantara Adisutjipto, 2020)
The analog AC-voltmeter usually can only measure the ideal-sinusoid voltage with narrow frequency range. Meanwhile, in fact the grid voltage is often not in the form of an ideal sinusoidal. To be able to measure a non-sinusoidal AC voltage with a wide range of frequency, a true-RMS voltmeter is needed. The research designed a true RMS measuring system using an ATmega 328P microcontroller. The input voltage is converted to pulse using Schmit triger and fed to the microcontroller’s external interrupt pin to calculate the input signal frequency. Meanwhile the microcontroller’s ADC sampled the input signal with a frequency of 128 times the signal’s frequency. RMS voltage calculations are performed using arithmetic operations for 16 and 32 bit integer variables. The test results show that the system can measure voltages with zero errors from 100 to 275 volts with a frequency of 50 Hz. The system can also measure voltages with zero errors at 220 volt with frequencies from 40 Hz to 150 Hz. However, this system can still be used to measure voltages ranging from 25 volts to 300 volts at frequencies from 35 Hz to 195 Hz with an average error of 0.21%. During RMS voltage calculation, the microcontroller’s CPU usage was 13.35%, so that this system can be further developed.